2001
DOI: 10.1029/2000jd900398
|View full text |Cite
|
Sign up to set email alerts
|

The impact of the mixing properties within the Antarctic stratospheric vortex on ozone loss in spring

Abstract: Abstract. Calculations of equivalent length from an artificial advected tracer provide new insight into the isentropic transport processes occurring within the Antarctic stratospheric vortex. These calculations show two distinct regions of approximately equal area: a strongly mixed vortex core and a broad ring of we. akly mixed air extending out to the vortex boundary. This broad ring of vortex air remains isolated from the core between late winter and midspring. Satellite measurements of stratospheric H20 con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
79
0

Year Published

2001
2001
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 72 publications
(88 citation statements)
references
References 30 publications
9
79
0
Order By: Relevance
“…As we have mentioned before, this ozone reduction is caused by transport of ozone-depleted air from lower latitudes where the ozone depletion had already started. The delay observed on SPS is a result of the time the ozone-poor air takes to travel from 78 to 90 • S according to Lee et al (2001). These observational results are in excellent agreement with the evolution of losses versus latitude and time computed by the SLIMCAT 3-D chemical-transport model for the year 1996 and 480 K isentropic level (Lee et al, 2001).…”
Section: Ozone Distribution Within the Vortex: Belgrano Vs South Polesupporting
confidence: 77%
See 1 more Smart Citation
“…As we have mentioned before, this ozone reduction is caused by transport of ozone-depleted air from lower latitudes where the ozone depletion had already started. The delay observed on SPS is a result of the time the ozone-poor air takes to travel from 78 to 90 • S according to Lee et al (2001). These observational results are in excellent agreement with the evolution of losses versus latitude and time computed by the SLIMCAT 3-D chemical-transport model for the year 1996 and 480 K isentropic level (Lee et al, 2001).…”
Section: Ozone Distribution Within the Vortex: Belgrano Vs South Polesupporting
confidence: 77%
“…The delay observed on SPS is a result of the time the ozone-poor air takes to travel from 78 to 90 • S according to Lee et al (2001). These observational results are in excellent agreement with the evolution of losses versus latitude and time computed by the SLIMCAT 3-D chemical-transport model for the year 1996 and 480 K isentropic level (Lee et al, 2001). Moreover, the model also shows that accumulated ozone loss becomes equal at a equivalent latitude poleward of 74 • S by the beginning of October, as found in the observations.…”
Section: Ozone Distribution Within the Vortex: Belgrano Vs South Polementioning
confidence: 99%
“…Kawa et al [1997] have used aircraft observations in the vortex edge to show that reactive Cl is very sensitive to temperatures near 195 K. Midwinter temperatures at the vortex edge (60°S) are about 200 K, while the vortex center (80°-90°S) typically has temperatures below 190 K. A zonally symmetric ozone hole of 25 million km 2 would be at 64.4°S. Lee et al [2001] have shown that the polar vortex at 480 K is separated into a well-mixed zone in the equivalent latitude range of 70°-90°S, and a weakly mixed zone of approximately 60°-70°S. The hole edge is most sensitive to temperature and chemistry in this ''weakly'' mixed region.…”
Section: Dynamical Variationsmentioning
confidence: 99%
“…These stations are chosen because their observations were made in the Lee et al [2001] ''weakly'' mixed region. The 50-day diabatic trajectories are run using UKMO analyses.…”
Section: Trajectory and Chemistry Modelingmentioning
confidence: 99%
“…5b), align with the outer limits of regions of enhanced ozone loss (Lee et al, 2001;Bodeker et al, 2002). This provides motivation for updated analyses of trends in vortex attributes, such as BI, to provide context for recent reports of trends in ozone concentrations observed during September (e.g.…”
Section: Impacts Of Bifurcated Pv Gradientsmentioning
confidence: 63%